Bisphosphonates and osteoprotegerin as inhibitors of myeloma bone disease. - Croucher, P; Shipman, C; Van Camp, B; Vanderkerken, K (2003)
BACKGROUND: A major clinical feature in multiple myeloma is the development of osteolytic bone disease. The increase in bone destruction is due to uncontrolled osteoclastic bone resorption. Until recently the factors responsible for mediating the increase in osteoclast formation in myeloma have been unclear. However, recent studies have implicated a number of factors, including the ligand for receptor activator of NFkappaB (RANKL) and macrophage inflammatory protein-1alpha. The demonstration that increased osteoclastic activity plays a central role in this process and the identification of molecules that may play a critical role in the development of myeloma bone disease have resulted in studies aimed at identifying new approaches to treating this aspect of myeloma. METHODS: Studies have been performed to determine the ability of recombinant osteoprotegerin (Fc.OPG), a soluble decoy receptor for RANKL, and potent new bisphosphonates to inhibit the development of myeloma bone disease in the 5T2MM murine model of multiple myeloma. RESULTS: Fc.OPG was shown to prevent the development of osteolytic bone lesions in 5T2MM bearing animals. These changes were associated with a preservation of the cancellous bone loss induced by myeloma cells and an inhibition of osteoclast formation. Bisphosphonates, including ibandronate and zoledronic acid, were also shown to inhibit the development of osteolytic bone lesions in the 5T2MM model and alternative models of myeloma bone disease. CONCLUSIONS: Bisphosphonates and Fc.OPG are effective inhibitors of the development of osteolytic bone lesions in pre-clinical murine models of myeloma bone disease.